2018
DOI: 10.1097/rli.0000000000000469
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]Ga-Pentixafor PET/MRI for CXCR4 Imaging of Chronic Lymphocytic Leukemia

Abstract: [Ga]Ga-Pentixafor positron emission tomography/magnetic resonance imaging may possibly be useful for CXCR4-based CLL imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 28 publications
3
47
0
1
Order By: Relevance
“…Second, we only include several types of lymphoma in our study. In addition to the lymphomas included in the current study, chronic lymphocytic leukemia, acute lymphoblastic leukemia, and acute myeloid leukemia have been reported being positive on [ 68 Ga]pentixafor PET [4,[11][12][13]. In vitro studies with ow cytometry, reverse transcription-polymerase chain reaction, and immunohistochemical analysis also detected strong expression of CXCR4 in hairy cell leukemia, T cell lymphoblastic lymphoma/leukemia, Sézary syndrome, angioimmunoblastic lymphoma, and anaplastic large cell lymphoma [32][33][34][35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Second, we only include several types of lymphoma in our study. In addition to the lymphomas included in the current study, chronic lymphocytic leukemia, acute lymphoblastic leukemia, and acute myeloid leukemia have been reported being positive on [ 68 Ga]pentixafor PET [4,[11][12][13]. In vitro studies with ow cytometry, reverse transcription-polymerase chain reaction, and immunohistochemical analysis also detected strong expression of CXCR4 in hairy cell leukemia, T cell lymphoblastic lymphoma/leukemia, Sézary syndrome, angioimmunoblastic lymphoma, and anaplastic large cell lymphoma [32][33][34][35][36][37][38][39].…”
Section: Resultsmentioning
confidence: 54%
“…The rst clinical application of [ 68 Ga]pentixafor PET has been carried out in patients with non-Hodgkin lymphoma and multiple myeloma, which con rmed the CXCR4 expression in these lymphoproliferative diseases as a proof-of-concept [4]. Since then, most studies of [ 68 Ga]pentixafor were focused on evaluation of hematologic malignancies, for example multiple myeloma [1,[5][6][7], Waldenström macroglobulinemia/lymphoplasmacytic lymphoma [8,9], mucosa associated lymphoid tissue (MALT) lymphoma [10], chronic lymphocytic leukemia [11], and acute myeloid leukemia [12,13]. Some studies showed remarkable superiority of [ 68 Ga]pentixafor PET in detecting tumors and staging of the disease when compared with [ 18 F]FDG PET [5,7,8].…”
Section: Read Full Licensementioning
confidence: 99%
“…[ 68 Ga]Ga-Pentixafor for PET/CT was able to image disease manifestation in 10/14 patients with myeloid leukaemia [218] and in 23/34 patients in another study [219]. Further evaluations showed the applicability of [ 68 Ga]Ga-Pentixafor PET/CT to identify patients with CXCR4-positive acute myeloid leukaemia [220] and chronic lymphocytic leukaemia [221]. It is assumed that CXCR4-directed imaging might be more included in patient selection for corresponding therapeutic approaches rather than to evaluate disease extent.…”
Section: Chemokine Receptormentioning
confidence: 98%
“…More recently, [ 68 Ga]Ga‐Pentixafor‐PET/MRI with DWI has been investigated in a small series of patients with CLL, to determine whether this imaging technique can capture bone marrow involvement based on CXCR4 expression or diffusivity (see Fig. ).…”
Section: Leukemiamentioning
confidence: 99%